Students Perception of the Learning Climate (TAJ: Journal of Teachers Association, 2009)
The study was conducted to acquire the base line information about perception of learning climate of education environment. To assay the climate of the medical education in Dhaka medical college, the Medical Education Environment Measure (MEEM) questionnaire was administered, completed and returned to the researcher by the 50 students of third year MBBS. The analysis of this inventory showed that the students felt that the teaching was teacher centered, not concerned to develop their competence and problem solving skills. Teachers were authoritarian and not good at providing feedback but they did not ridicule the students. Most students' felt that they have made in right career choice but have not learned a lot about empathy in the profession. Students felt that politics, atmosphere in the classroom and in the hostels, and teacher student relationship as well as relations among the students themselves influenced the learning environment. doi: 10.3329/taj.v18i1.3298 TAJ 2005; 18(1): 17-24